Representation in Wales: an empirical analysis of the policy divisions between voters and candidates - Trumm, Siim (SAGE Publications, 2017)
Politics in Wales is often portrayed as being relatively consensual when compared with the rest of the United Kingdom and enjoying healthy levels of trust between voters and elites. Recent events like the decision of Welsh voters to reject the European Union membership against the advice of most of its political establishment, however, are calling to question this perception. Using 2016 Welsh Candidate Study and 2016 Welsh Election Study data, this paper evaluates the extent of policy divisions between voters and candidates in Wales. I find that candidates hold more liberal policy positions and are less likely to think of immigration as the most important policy priority. In addition, they tend to favour a different approach to parliamentary representation, deeming it more acceptable for Assembly Members to discard the views of their voters in favour of their own views or those of their party.